Ectopic thyroid in the hepatoduodenal ligament: a case report and literature review - Zhang, Lei; Cui, Xijun; Wang, Baolei; Du, Xiulan; Hou, Guoqi; Yu, Xiaoqian (Frontiers in Oncology, 2024)
Ectopic thyroid arises from abnormal development of thyroid primordial tissues as it migrates to the lower interstitium during the embryonic period, which can occur at various locations during the descent process. However, ectopic thyroid in the subdiaphragmatic area is extremely rare. In this case, we report a case of ectopic thyroid located in the hepatoduodenal ligament. The 60-year-old female patient was admitted to hospital with gallbladder stones and cholecystitis. Preoperative imaging showed a mass in the hepatoduodenal ligament. As the patient declined a needle biopsy of the mass, the nature of the mass remained unclear prior to surgery. The patient subsequently underwent laparoscopic cholecystectomy and exploratory resection of the mass. The histopathology of the resected mass showed the characteristics of ectopic thyroid, and immunohistochemical staining revealed positive expression of thyroid transcription factor-1 and thyroglobulin. The diagnosis of ectopic thyroid was established. Upon confirming the diagnosis, comprehensive neck examination revealed the presence of a normally functioning thyroid gland. Throughout the four-year follow-up period, the patient's thyroid ultrasonography and thyroid function tests indicated no abnormalities. Ectopic thyroid in the hepatoduodenal ligament and surrounding areas is an extremely rare clinical abnormality, achieving a clear diagnosis before initiating treatment offers diagnostic and treatment insights and clues for clinicians when differentiating masses within this region.